Nikah dalam Perspektif Al-Qur’an (Telaah Tematik atas Ayat-Ayat tentang Nikah) - Ridwan Sahrani; Muhammad Yusuf; Mardan Mardan; Abdul Rachman Sahrani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Marriage is a sacred institution in Islam that functions not only as a physical bond between a man and a woman, but also embodies profound spiritual, moral, and social values. This study aims to analyze the concept of marriage in Islam through both normative and contextual approaches. The research uses a qualitative method with library research as the primary approach. Data sources include the Qur’an, Hadith, classical and contemporary fiqh literature, and Islamic family law documents in Indonesia. The findings reveal that marriage in Islam represents the implementation of maqāṣid al-sharī‘ah, particularly in preserving lineage, honor, and religion. On the other hand, various social phenomena—such as early marriage, unregistered marriages without valid guardians, and rising divorce rates—indicate a significant gap between normative teachings and social practices. Therefore, an educational approach and continuous community development are essential to restore the ideal function of marriage in Islam as the foundation of a dignified family and society